Les mots de la religion et de la superstition dans le Dictionnaire Languedocien d’Augustin Bonet (xviiie siècle) - Claire Torreilles (Revue des Langues Romanes)
In this work, the numerous quotations derived from various 17th century Occitan religious writings (La Bido de sant Benoist by Bernard Grimaud, L’exercici de la fe by Barthélémy Amilha) show a humanist scholar as concerned with religious instruction from a post-Tridentine standpoint as with the study of the Occitan language as such and its literature. From Grimaud’s Virgilian digressions to Amilha’s famous canticles, the excerpts chosen to illustrate the definitions of the headwords provide a genuine poetic pleasure. But the people’s own language is also imbued with creeds and superstitions, the most delightful descriptions of which he quotes (rites and blasphemous prayers, Saint John’s Night bonfires and Saint John’s Wort) while morally condemning them in the name of faith and reason, on the model of Jean-Baptiste Thiers’s Traité des superstitions, which he often refers to. By focusing his scholarship on popular culture, Bonet, whose dictionary was lost for over two centuries, proved to be a pioneer.